The Effect of ESG Performance and Sustainability Reporting on Firm Value: Evidence from Mining Companies in Indonesia - Fityan Izza Noor Abidin; Endra Wahyu Ningdiyah; Wiwit Hariyanto (International Journal on Orange Technologies, 2026)
This study aims to analyze the effect of Environmental, Social, Governance (ESG) and Sustainability Reporting on Firm Value in mining companies in Indonesia. This study uses secondary data obtained from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX), with a total sample of 39 companies. The analytical method used is multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, the data were tested using classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The dependent variable in this study is Firm Value measured using Tobin’s Q, while the independent variables consist of ESG and Sustainability Reporting. The results show that ESG has a positive and significant effect on Firm Value. This indicates that better ESG performance leads to higher firm value from investors’ perspective. In addition, Sustainability Reporting also has a positive and significant effect on Firm Value, indicating that companies that disclose sustainability reports tend to have higher firm value. Simultaneously, ESG and Sustainability Reporting have a significant effect on Firm Value. The coefficient of determination shows that ESG and Sustainability Reporting explain 84.5% of the variation in Firm Value, while the remaining is explained by other variables outside the research model.